A new species of Otacilia Thorell, 1897 (Araneae, Phrurolithidae) from Tongboshan National Nature Reserve, Jiangxi Province, China - Zimin Jiang; Changyong Lin; Zhongjing Wang; Yanbin Yao; Keke Liu (Biodiversity Data Journal)
Sixty-four phrurolithid species were found from Jiangxi Province in the past five years. However, there are still many unknown phrurolithid species from this Province with unusual morphological characteristics.A new species, Otacilia tongboshan Liu, sp. nov. is described from Tongboshan National Nature Reserve, Jiangxi Province, China. Morphological illustrations, SEMs and living photos and a distribution map are given.